Vörner syndrome. Different stages of clinical manifestation in an Indian family. - Biswal, S.G.; Mehta, R.D. (European Journal of Pediatric Dermatology, 2015)
Palmoplantar keratoderma Vörner is an inherited autosomal dominant disease usually due to a mutation of the gene coding for keratin 9, which is specific for the palmo-plantar skin. It is histologically characterized by epidermolytic hyperkeratosis. Here is reported an Indian family showing the different clinical features of the disease.